Pastures and Forage Crops for Horses - Yoana C. Newman; Edward L. Johnson; Joao Vendramini; Carol Chambliss; Ikechukwu V. Ezenwa (EDIS)
Revised! SS-AGR-65, an 8-page fact sheet by Y. C. Newman, E. L. Johnson, J. Vendramini, C. Chambliss, and I. V. Ezenwa, discusses site selection, stocking rate, varieties, and pasture management for horses. Published by the UF Department of Agronomy, September 2010.